BRANDING SERIAL KKPK: TINJAUAN PADA MINAT LITERASI ANAK-ANAK - Redjeki Agoestyowati (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
Based on the results of a survey of literacy index published by Central Connecticut State of the University (CCSU) in March 2016 showed from 61 countries surveyed, Indonesia's literacy rankings are in the 60th sequence. The research also assessed the reading assessment score for children under the age of 18 , as quoted from page CCSU.edu (accessed 4/6/2017) shows that the ability of Indonesian children to understand the reading is also very low.Children's literacy skills can be very high. That means, the family and the form of early childhood education have a very big influence on the high-low literacy ability of a child.The publisher of Mizan through KKPK / Kecil-Kecil Punya Karya, is a pioneer of quality reading books written by Indonesian children. In KKPK's book, the writings published are children's writing from 7-12 years old, which also corresponds to a focused market share. Based on the point of view, the purpose of this study is to examine the branding of KPPK in the perspective of increasing the interest of children literacy. From the study of literature research methods conducted by the author, it is concluded that Dar Mizan Publisher through KKPK book has made a strong branding as a pioneer of book publishers that provides a container for children to publish their writing visually. The opportunity to write visual works is support for one's literacy skills, especially children. In this case, Dar Mizan Publisher, through KKPK book has increased interest and literacy ability of children. KKPK has become a medium to improve the literacy ability of children with earlier.